Physiological evaluation of PVP-coated AgNP in the rat small intestine: an ex vivo approach - Chávez-Hernández, Jorge Antonio; España-Sánchez, Beatriz Liliana; Aguirre-Bañuelos, Patricia; Granados-López, Lucero; Velarde-Salcedo, Aída Jimena; Luna-Bárcenas, Gabriel; Gonzalez, Carmen (Frontiers in Nanotechnology, 2024)
Silver nanoparticles (AgNP) are widely used globally due to their numerous properties, mainly because of their antimicrobial activity. However, the need for further regulations and legislation regarding their presence in products has led to concerns about their biosecurity, making relevant biological studies at different levels. The present work aimed to evaluate the effect of the PVP-coated AgNP upon the small intestine muscle tone or continuous partial contraction state, and the mediators involved (nitric oxide and serotonin) in an ex vivo model. Intestinal segments (duodenum, jejunum, and ileum) were treated in the presence and absence of five cumulative increasing concentrations of AgNP (0.01, 0.1, 1, 10, 100 μg/ml) and three individual concentrations of PVP coated-AgNP (0.01, 1 & 100 μg/ml), showing a transient decrement on the contractile effect in the small intestine segments treated with cumulative increasing concentrations. This effect did not allow the isolated small intestine rings to return to their contractile basal level, and it was associated with an increment of nitric oxide (NO) production and variations in the amount of serotonin. Similar effect was observed at individual AgNP administrations but with a lesser influence on NO production. These results show that AgNP, in the function of the administration (cumulative or individual) and the segment type, can modify the muscle tone of the small intestine mediated in part by NO and exerting a differential pattern in the amount of serotonin. Histological analysis revealed specific morphological alterations induced by AgNP, like necrosis and villi detachment, were more evident in the ileum segment. Furthermore, the accumulation of silver was observed in the small intestine villi, which could determine the physiological effects exerted upon the muscle tone associated with the release of specific mediators like NO production and the presence of serotonin. These findings suggest that the small intestine is an essential target of the actions induced by AgNP, which could be ingested and reach this conduit because of the consumption of products containing these materials, modifying the intestinal motility that influences the efficiency in nutrient absorption, aspects that need to be explored and investigate in the short, medium, and long term.